From precipitation to ice core: On the importance of surface processes for stable water-isotope records in East Antarctica - Inés Ollivier; Hans Christian Steen-Larsen; Mathieu Casado; Barbara Stenni; Amaelle Landais (Past Global Changes Magazine, 2023)
Stable water-isotope records from Antarctic ice cores allow the reconstruction of past temperature variability. However, accurate interpretation of the isotopic signal requires comprehensive understanding of the processes leading to its archiving in snow and ice, which can be documented by in situ measurements.